GFP is heritable, but what is it? - Vukasović, Tena; Bratko, Denis; Butković, Ana (2013)
In recent years, there has been a lot of discussion on the (non)existence of a general factor of personality (GFP). Some claims have been made for a general factor of all personality traits, but there have also been some critiques of the construct. Some authors believe it is time to consider what is a general factor and how to estimate it. The aim of this study was to try and replicate previous studies of heritability of GFP in a sample of Croatian twins. Data on personality, measured by NEO-FFI, was collected from 339 twin pairs (105 MZ and 234 DZ), aged between 15 and 22 years. The GFP was formed as a first unrotated factor, with factor loadings in line with those obtained in previous studies. Intraclass correlations on GFP were 0.66 for MZ and 0.24 for DZ twins, indicating a dominance effect. Univariate analysis, performed in Mx, indicated that genetic factors contributed around 66% to individual differences in GFP. Additional analyses were performed on the phenotypic level, as proposed by Revelle and Wilt (2012). Exploratory factor analysis approach to ﬁnding ωh through a Schmid-Leiman transformation has shown that explained common variance of the GFP was only 22% and ωh was 0.20. Results will be interpreted in line with some critiques of procedures used for estimating the GFP.
Projekt MZOS
ENG